The Effects of Concentrate Supplement Levels on Feed Utilization and Red Meat Production of Blackhead Somali Sheep Fed Natural Pasture Grass Hay as a Basal Diet - Shashie Ayele Yimenu; Mengistu Urge Letta (Veterinary Medicine and Science)
ABSTRACT Background In recent years, consumers have become aware of their health, and their preference has been rapidly changing to consume less fatty meat. Therefore, devising a strategy to produce lean meat is a concern in this study. One of the strategies, among others, for lean meat production is controlling the amount of supplements given to sheep. Hence, muscle (lean) and adipose tissue (fat) require different amounts of energy to lie down. Objectives This study was conducted to evaluate the effects of concentrate supplementation levels on feed utilization and red meat production in Blackhead Somali sheep (BHS) fed natural pasture grass hay as a basal diet. Materials and Methods A total of 16 BHS sheep weighing 19.5 ± 0.2 kg (mean ± SE) at the beginning of the experiment were kept for 90 days by feeding two levels (1% [T1] and 1.75% [T2] body weight [BW] of sheep) of supplement. The sheep were blocked according to their initial BW (IBW), and the supplements were randomly assigned within a block. At the end of the feeding period, all sheep were slaughtered, and carcass and non‐carcass data were recorded. Data were analysed using the SAS software version 9.1 of PROC GLM programme. Results Sheep fed T1 and T2 consumed 6.1 and 8.2 MJ/day metabolizable energy (ME), respectively, and 73.1 and 93.6 g/day crude protein (CP), in that order. Consequently, sheep fed T2 produced 1.37 kg extra BW by growing an average rate of 15 g/day greater (p < 0.0001) over their counterpart fed T1. They also produced 0.9 kg, 0.8 cm2 and 2.64% heavier carcasses, a wider rib eye area and a higher intramuscular fat content (p < 0.0001), respectively, over the sheep fed T1. On the other hand, the lean‐to‐fat ratio was significantly lower in sheep fed T2 than T1. In most parameters considered in this study, sheep fed T2 (1.75% BW) were superior, but its intramuscular fat (IMF) content was much higher than the limit that the consumers needed. Conclusion Therefore, it can be concluded that 1% BW supplementation is enough for BHS to produce lean meat containing the optimal fat content in stall feeding condition.